Barriers to morphine use in primary care in the Cape Town metropole - Hofmeyr, Graeme (Department of Public Health and Family Medicine, 2024)
Background Access to oral morphine is an essential element of palliative care services, and a useful indicator of the availability of those services. The South African National Policy Framework and Strategy on Palliative Care 2017- 2022 envisages a system in which palliative care is widely available in the primary healthcare or community setting. If this is to be achieved an analysis of the morphine use patterns withing the health system, and the development of indicators to monitor implementation are vital. Aim The aim of this research was to examine the patterns of oral, outpatient morphine prescription in public healthcare facilities within the Cape Town Metropole, and to develop methods to compare the patterns of oral morphine use between primary care facilities, district hospitals and tertiary hospitals. Setting The setting of this study is the public healthcare system in the Cape Town Metropole during the period 2016- 2018. Methods In this descriptive analysis a dataset was generated from routinely collected prescribing and outpatient headcount information to allow an analysis of morphine prescribing patterns within the Metro, and comparison both between facilities and levels of care. Results The rate of morphine prescription was much higher at the two tertiary facilities (605.2 episodes/100 000 outpatient visits) than at District Hospitals or at Primary Care (182.1 and 56.6 episodes/100 000 outpatient visits respectively. There was considerable variation between prescribing rates of facilities at the same level of care. Conclusion Access to oral morphine at the primary care level is limited and needs to be improved if South Africa is to successfully implement local and international guidelines on the provision of palliative care at the primary and community level. The ratio of morphine prescription to outpatient visits allows useful comparisons to be made between access to palliative care services at healthcare service levels and individual facilities.